Ictal High-Frequency Oscillation for Lateralizing Patients With Suspected Bitemporal Epilepsy Using Wavelet Transform and Granger Causality Analysis - Han, Tao; Xu, Zhexue; Du, Jialin; Zhou, Qilin; Yu, Tao; Liu, Chunyan; Wang, Yuping (Frontiers in Neuroinformatics, 2019)
Indentifying lateralization of bilateral temporal lobe epilepsy (TLE) is a challenging issue, scalp electroencephalography (EEG) and routine band electrocorticography (ECoG) fail to reveal the epileptogenic focus for further temporal lobectomy treatment. HFOs can be utilized as a biomarker for lateralizing the onset zone in suspected bitemporal epilepsy. Except subjective vision detect the HFOs, objective verification should be performed to raising the accuracy. In present research, we prospectively studied 10 patients with refractory temporal seizures and underwent electrocorticography (ECoG) with wide-band frequency amplifiers (2048Hz), all patients had a Class I outcome after temporal resection. Pre- and ictal HFOs will be analyzed by wavelet transform (WT) and Granger causality (GC) for objectively verifying lateralization of seizure onset zone (SOZ). WT analysis showed ictal HFOs in 10 patients mainly covered from 80Hz to 115 Hz (average, 92.59 ± 10.23Hz ), and there was distinct band-pass boundary between pre-ictal HFOs and ictal HFOs. GC analysis showed 5 patients (2, 4, 5, 6, 7), no matter pre-ictal or ictal state, had highest GC degree in SOZ itself. The remaining patients (1, 3, 8, 9, 10) had highest GC degree in SOZ with its adjacent regions in pre-ictal and ictal stage. GC analysis further confirmed the result of WT, and suggested HFOs is initiated and propagated in local brain region mainly, afterwards, transmitting to adjacent brain regions. These results indicated that combination of WT and GC analysis significantly contribute to accurate lateralizing patients with suspected bitemporal epilepsy.